Relationship between emotional regulation, friendship quality and media violence exposure and aggressive behaviour among primary school children in Selangor - Kong, Luo Lan (2013)
This study aimed to investigate the relationship between emotional regulation, friendship quality, media violence exposure and aggressive behaviour among primary school children. The study employed a correlational research design and the data was analyzed using descriptive and inferential statistics to address the research objectives. A total of 450 students aged 11 years old were randomly selected from nine schools in the Selangor districts to participate in this study. Four instruments were used to measure the variables in this study; they were Children Aggression Inventory (CAI) to measure the tendencies of aggressive behaviour among children; Cognitive Emotional Regulation Questionnaire-Kids (CERQ-k) to measure emotional regulation of children; Friendship Quality Scale (FQS) to measure the quality of friendship, and Violent Media Exposure (MVE) to measure the violent video game exposure and violent TV programme exposure. Findings showed that most of the children demonstrated a moderate aggression level. The mean scores for the aggressive behaviour exhibited by children in descending order from high to low are hostility, anger, verbal aggression, indirect aggression, and physical aggression. An independent-samples t-test was utilised to determine the gender difference in aggressive behaviour. The result found that there was no significant difference in the mean aggressive behaviour score for boys and girls. In addition, the Pearson correlation was employed to examine the relationship between emotional regulation, friendship quality, video game violent exposure, TV programme violent exposure, and aggressive behaviour. Findings showed that emotional regulation was moderately associated with aggressive behaviour. Friendship quality was negatively related with children’s aggressive behaviour. The study also found that video game violence exposure and TV programme violence exposure were positively correlate with aggressive behaviour among children. The multiple linear regression (Enter Method) was used to determine the best set of predictor variable in predicting children’s aggressive behaviour. The multiple linear regression findings showed that the two predictor variables explain about 19.10% of the variance in children’s aggressive behaviour, with emotional regulation as the strongest predictor. The evidences from this study support the idea that emotional regulation, violent video game exposure, and violent TV programme exposure link to children’s aggressive behaviour. From this we can conclude that as the ability to regulate emotions increase,children are fewer tendencies to behave aggressively. In addition, the more they exposed to violent video game playing and violent TV programme viewing, they are more likely to behave aggressively. Thus, the findings from this study ameliorated the understanding of the influence of emotional regulation, video game violence exposure, and TV program violence exposure on children’s aggressive behaviour to policy makers, researchers, teachers, counsellors, parents, students, and the community so that holistic strategic measures could be implemented to keep children aggression at bay. Intervention programs such as promoting ability of regulate emotions and introduce emotional regulation activities curbing aggressive behaviour among children is highly recommended.